Reevaluation of risk factors for time to subsequent events after first stroke occurrence using a new weighted all-cause effect measure - Ozga, Ann-Kathrin; Rauch, Bernhard; Palm, Frederick; Urbanek, Christian; Grau, Armin J.; Becher, Heiko; Rauch, Geraldine (BMC public health, 2020)
Risk diseases and risk factors for stroke include atrial fibrillation, hypertension, diabetes mellitus, smoking, and elevated LDL-cholesterol. Due to modern treatment options, the impact of these risk diseases on subsequent cardiovascular events or death after a first stroke is less clear and needs to be elucidated. We therefore aimed to get insights into the persistence of adverse prognostic effects of these risk diseases and risk factors on subsequent stroke or death events 1 year after the first stroke by using the new weighted all-cause hazard ratio.
Gesehen am 15.10.2020